Phytochemical, pharmacological activity and molecular docking investigations of Tetracera indica (Christm. & Panz.) Merr., Averrhoa bilimbi Linn. and Gymnanthemum glaberrimum (Welw. ex O.Hoffm) H. Rob - Alhassan, Muhammad Alhassan (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Tetracera indica and Averrhoa bilimbi are used in traditional treatment of diabetes mellitus while Gymnanthemum glaberrimum is used as a remedy for skin cancer. The objectives of the present study were to investigate the pharmacological activity of leaves of T. indica, G. glaberrimum and A. bilimbi, and their phytochemical constituents. Ethanol extract from the leaves of T. indica was subjected to α-glucosidase inhibitory activity evaluation and isolation of bioactive compounds followed by molecular docking. Methanol extract of G. glaberrium leaves was subjected to cytotoxic investigations on A375, HT-29 and MCF7 cancer cell lines, followed by isolation of bioactive constituents and molecular docking. Purified compounds were characterized using spectroscopic analysis. Furthermore, the antioxidant activity of methanol extract of A. bilimbi leaves and its fractions was investigated and the active compounds were identified by LC-MS-QTOF analysis. Nine compounds were isolated from T. indica leaves which include; lupeol, betulinic acid, wogonin, norwogonin, quercetin, tectochrysin, kaempferol and two new sulphated flavones viz. 5,7-dihydroxyflavone-O-8-sulphate and 5-hydroxy-8-methoxyflavone-O-7-sulphate. Quercetin, kaempferol and 5,7-dihydroxyflavone-O-8-sulphate showed significant (P<0.05) α-glucosidase inhibitory activity with IC50 values of 61.86 ± 2.4, 68.46 ± 3.5 and 133.57 ± 5.2 μM respectively, compared to acarbose (IC50 419.42 ± 20.29 µM). Molecular docking result showed favourable mode of interactions of these flavonoids in the active site of α-glucosidase. Furthermore, four compounds viz. nonacosanoic acid, lupeol, 5-methylcoumarin-4-β-glucoside and 4-hydroxy-5-methylcoumarin were isolated from G. glaberrimum. Lupeol displayed significant (P<0.05) antiproliferative effect against MCF-7 cell lines with IC50 of 34.15 ± 2.32 µg/mL. Lupeol and 5-methylcoumarin-4-β-glucoside displayed moderate cytotoxic effect on A375 cells with IC50 of 59.18 ± 2.70 and 91.84 ± 6.78 µg/mL. 4-Hydroxy-5-methylcoumarin, and lupeol displayed significant (P<0.01) cytotoxic effect on HT-29 cells with IC50 of 4.22 ± 0.13, 15.24 ± 1.15 µg/mL respectively, which is comparable with 5-fluorouracil (IC50 8.00 ± 0.78 µg/mL). CDK2 receptor and CA IX and XII were identified through molecular docking as potential target for these compounds. The n-butanol fraction of A. bilimbi extract displayed significant (P<0.05) DPPH radical scavenging effect with IC50 (4.14 ± 0.21 μg/mL). It also exhibited significant (P<0.05) XO inhibitory effect with IC50 of 64.84 ± 3.93 μg/mL. Afzelechin 3-O-alpha-L-rhamnopyranoside and cucumerin A were identified through LC-MS-QTOF as possible metabolites responsible for the antioxidant activity of the n-butanol fraction.